TAMAN BACA PUSTAKA SEBAGAI PERLUASAN LAYANAN PERPUSTAKAAN KHUSUS BERBASIS INKLUSI SOSIAL - Gresia Bernika Br Sembiring (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. Library as a lifelong learning place for the community has an important role in improving the quality of people's lives.Purpose. This study discusses how the librarian's response to the library program based on social inclusion and three things as a basic of a special library to become a social inclusion-based library. The purpose of this study is to describe and explain how the Ministry of Agriculture's library can play a role in national development programs related to community empowerment through social inclusion-based library.Method. The study was conducted with a qualitative approach with a case study method. Data was collected by observation and interviews.Results and discussions. The results of the research is that PUSTAKA established Taman Baca Pustaka as a social inclusion-based library as a model proposed by Faulkner, that PUSTAKA as a special library meets the minimum requirements for the development of social inclusion-based library namely resources, capacity, and opportunities. Besides, PUSTAKA also organizes programs that actively involve the community as a response and support for social inclusion-based library policies for improving the quality and welfare of the community.